y-9=-5(x+6)

Simple and best practice solution for y-9=-5(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-9=-5(x+6) equation:


Simplifying
y + -9 = -5(x + 6)

Reorder the terms:
-9 + y = -5(x + 6)

Reorder the terms:
-9 + y = -5(6 + x)
-9 + y = (6 * -5 + x * -5)
-9 + y = (-30 + -5x)

Solving
-9 + y = -30 + -5x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + y = -30 + 9 + -5x

Combine like terms: -9 + 9 = 0
0 + y = -30 + 9 + -5x
y = -30 + 9 + -5x

Combine like terms: -30 + 9 = -21
y = -21 + -5x

Simplifying
y = -21 + -5x

See similar equations:

| 3(9y+3)-11=2y+21 | | -6X+-36=-6x+-3 | | 2x+(3+4)=52 | | ax+d=c-bx | | 60n=(-12) | | -6X+36+2=-6x+-3 | | x+b=c-z | | 9a-(-72)=-8 | | -6=3y-21 | | 4k=-2k+18 | | 8=cups | | (0.25)X-1=32 | | 10e-6=14 | | 5.23x+10.46=20.92 | | 7+5x-3x=13 | | 9-3(2g+2)= | | 13x-17=9x-15 | | 12*5n=0 | | 40x-26x^2+4x^3=0 | | 2(4-3x)=8 | | x+20=52 | | y-36=7 | | 8(8-4)=-2(x+6) | | 8y-4y-5=61.84 | | 4(x+9)=30 | | -8=2v+4 | | 10X+14+8= | | 7(4k+11)= | | 8x+12+60=180 | | -7x+3=-7x+5 | | 22+5(x+3)= | | 2x+0=0x-2 |

Equations solver categories